Foliar fertilization and thinning of Ponkan tangerine trees (Citrus reticulata Blanco) on the quality of the fruits - Gazzola, Rosaura; de Souza, Mauricio (Pesquisa Agropecuaria Brasileira, 1994)
This work aimed to assess the effects of thinning and foliar fertilization of tangerine trees on quality of the fruits. The experiment was carried out in a grove of seven-years old ’Ponkan’ tangerine trees on Rangpur Lime like rootstocks located at Escola Superior de Agricultura de Lavras, Minas Gerais State, Brazil. Treatments consisted of five levels of thinning (10, 8, 5, 3 and 1 fruit/branch) and four different schedules for foliar fertilization (0, 4, 8 and 12 applications). The statistical design was randomized blocks, in a factorial scheme, with five replications. Experimental plots consisted of one branch with ten fruits. Foliar fertilization, with a commercial formulation containing chelated N, Mg, S, B, Mn and Zn, were carried out at 12 day intervals. Thinning increased the longitudinal diameter and weight of the fruits. The interaction between thinning and foliar fertilization affected the soluble solids/acidity ratio, which was highest for branches with one fruit.